GOVERNING SHADOWS: INSTITUTIONAL AND FISCAL INFLUENCES ON ECONOMIC FORMALITY IN THE EU - MASTAC LAVINIA; VANCEA DIANE PAULA CORINA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
This study investigates the interplay between institutional quality, tax policies, digitalization, and the informal economy across the European Union and two European Union adjacent countries. Principal Component Analysis (PCA) is used for the investigation. The study elucidates two main dimensions: the correlation between institutional robustness and digitalization, and the association of tax efficiency with economic compliance. The findings indicate that nations with strong institutions, minimal corruption, and sophisticated digital infrastructures, such as Denmark, Sweden, and Finland, are characterized by smaller informal economies and higher tax compliance rates. In contrast, countries like Romania, Bulgaria, and Slovakia, which contend with institutional weaknesses, show elevated levels of informality and reduced tax compliance. The study recommends prioritizing governance reforms aimed at improving administrative efficiency and transparency in nations with frail institutional structures before implementing digital tax solutions. Simultaneously, countries with moderate institutional capabilities but inefficient tax collection systems could benefit from immediate digital enhancements. Overall, this research advocates for an integrated policy framework that marries institutional strengthening with digital innovations to foster economic transparency and enhance public revenue collection, paving the way for sustainable economic development within the European Union.